Preclinical evaluation of RNAi as a treatment for transthyretin-mediated amyloidosis. (2nd April 2016) - Butler, James S.; Chan, Amy; Costelha, Susete; Fishman, Shannon; Willoughby, Jennifer L. S.; Borland, Todd D.; Milstein, Stuart; Foster, Donald J.; Gonçalves, Paula; Chen, Qingmin; Qin, June; Bettencourt, Brian R.; et al.
Abstract: ATTR amyloidosis is a systemic, debilitating and fatal disease caused by transthyretin (TTR) amyloid accumulation. RNA interference (RNAi) is a clinically validated technology that may be a promising approach to the treatment of ATTR amyloidosis. The vast majority of TTR, the soluble precursor of TTR amyloid, is expressed and synthesized in the liver. RNAi technology enables robust hepatic gene silencing, the goal of which would be to reduce systemic levels of TTR and mitigate many of the clinical manifestations of ATTR that arise from hepatic TTR expression. To test this hypothesis, TTR-targeting siRNAs were evaluated in a murine model of hereditary ATTR amyloidosis. RNAi-mediated silencing of hepatic TTR expression inhibited TTR deposition and facilitated regression of existing TTR deposits in pathologically relevant tissues. Further, the extent of deposit regression correlated with the level of RNAi-mediated knockdown. In comparison to the TTR stabilizer, tafamidis, RNAi-mediated TTR knockdown led to greater regression of TTR deposits across a broader range of affected tissues. Together, the data presented herein support the therapeutic hypothesis behind TTR lowering and highlight the potential of RNAi in the treatment of patients afflicted with ATTR amyloidosis.